Catheter Aspiration With Recanalization for Budd-Chiari Syndrome With Inferior Vena Cava Thrombosis. Issue 4 (August 2019) - Yang, Fang; Huang, Ping-Chao; Yan, Lei-Lei; Zhang, Ze-Dong; Fu, Yu-Fei; Xia, Feng-Fei
Abstract : Purpose: To assess the safety and clinical effectiveness of catheter aspiration with recanalization in patients with Budd-Chiari syndrome (BCS) and inferior vena cava (IVC) thrombosis. Materials and Methods: Between January 2010 and December 2017, 33 patients with BCS and IVC thrombosis were treated by catheter aspiration with IVC recanalization in our center. A 12 F angled-tip guiding catheter was used for the aspiration of thrombi in the IVC. Recanalization was conducted following thrombi aspiration. Rates of technical success, clinical success and long-term patency were calculated. Results: Catheter aspiration with IVC recanalization was technically successful in all patients. After aspiration, no thrombi were detectable by IVC venography in 21 patients, while residual mural thrombi were found in 12 patients. IVC balloon dilation was performed in 18 patients, while stent insertion was performed in 15 patients. We also achieved clinical success in all patients. Symptomatic and asymptomatic pulmonary embolism were found in 1 patient each, respectively. The cumulative 1-, 3-, and 5-year patency rates were 93.6%, 93.6%, and 83.2%, respectively. All patients remained alive during the follow-up. Conclusions: Catheter aspiration with recanalization is a safe and efficacious approach to treating patients with BCS and IVC thrombosis.